Collaborative care: Primary health workforce and service delivery in Western New South Wales—A case study. (29th September 2021) - Ramsden, Robyn; Davies, Sarah; Colbran, Richard; Haigh, Amelia; Connors, Meegan; Nott, Shannon; Lowe, Estrella; Edwards, Michael; Clegg, Richard; Bagnulo, Sharif; Pit, Sabrina
Abstract: Objective: To explore how four small towns in rural New South Wales known as the 4Ts are addressing challenges accessing quality care and sustainable health services through a collaborative approach to workforce planning using the collaborative care framework. Design: Descriptive case study approach. Setting: The collaborative care project was developed as a result of ongoing partnerships between 2 rural Local Health Districts, 2 Primary Health Networks and a non‐governmental health workforce organisation. The collaboration works with 5 subregions each comprising 2 or more rural communities. This paper focuses on the 4Ts subregion. Participants: Stakeholders of the collaborative design including organisations and the community. Intervention: A place‐based approach to co‐designing health services with community in one sub‐region of Western New South Wales. Main outcome measures: A synthesis of field observations and experiences of community and jurisdictional partners in implementation of the 4Ts subregional model. Mapping of implementation processes against the collaborative care framework. Results: The collaborative care framework is a useful planning and community engagement tool to build health workforce literacy and to impact on system change at the local level. We identify key elements of effectiveness in establishing the 4Ts model, including the need for coordinated health system planning, better integrating existing resources to deliver services, community engagement, building health workforce literacy and town‐based planning. Conclusion: This study adds to the body of knowledge about how to successfully develop a collaborative primary health care workforce model in practice. The findings demonstrate that the implementation of a collaborative primary health care workforce model using the collaborative care framework can improve service access and quality, which in turn might facilitate workforce sustainability.